Pendampingan Pemanfaatan Lahan Pekarangan Sebagai Persediaan Obat Herbal Keluarga Desa Sudimoro Bululawang Malang - Husni, Muhammad (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The implementation of this Community Service was carried out from January 07 2023 to March 19 2023 in Sudimoro Village going well. The purpose of this service is to explain the use of yard land in RT 19 Sudimoro Village Making TOGA a supply of family the herbal medicines in RT 19 Sudimoro Village. the Participatory Action Research (PAR) service method carried out in the implementation of community service includes: Observation (observation), Action (action). Reflection The result is the result obtained from this service in the village of Sudimoro. The community members are starting to understand the importance of utilizing the empty yards they have around their house. One of the positive activities they do’s to plant medicinal plants to provide natural medicine. for their families. So that. the use of natural medicines can be cultivated. this activity can help the empowered people in preserving the use of vacant land by cultivating medicinal plants as natural medicines for families. The medicinal plants are seen to have advantages compared to chemical drugs in circulation such as not having side effect, easy to prepare, easy to get and the price is cheaper